OVID'S SCRIPTA PUELLA: PERILLA AS POETIC AND POLITICAL FICTION IN TRISTIA 3.71. - INGLEHEART, JENNIFER (Classical Quarterly, 2012)
A criticism is presented of the Latin elegiac poetry of Ovid known as the "Tristia," in which the author explores the role of the "scripta puella," a female poetic construct that reflects the male poet's needs, and the role of the character of Perilla in particular within the context of Latin elegy. Topics include Ovid's exile by Roman Emperor Augustus, Ovid's depiction of Camilla in his poetic work entitled "Amores," and Augustus' relationship with Roman poetry.